2016
DOI: 10.1016/j.addma.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fatigue crack growth behavior in LENS fabricated Ti-6Al-4V using high-energy synchrotron x-ray microtomography

Abstract: Laser Engineered Net Shaping (LENS) is an additive manufacturing technique that belongs to the ASTM standardized directed energy deposition category. To date, very limited work has been conducted towards understanding the fatigue crack growth behavior of LENS fabricated materials, which hinders the widespread adoption of this technology for high-integrity structural applications. In this study, the propagation of a 20 µm initial crack in LENS fabricated Ti-6Al-4V was captured in-situ, using highenergy synchrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…The microstructure of LMD-fabricated Ti-6Al-4V components is composed of acicular α' martensite. Figure 7a,b shows such a microstructure as was also described in other studies [14][15][16][17]20]. The α' martensitic microstructure produced after LMD manufacturing of Ti-6AL-4V is located inside the elongated prior β grains.…”
Section: Laser Metal Deposition (Lmd)supporting
confidence: 77%
See 1 more Smart Citation
“…The microstructure of LMD-fabricated Ti-6Al-4V components is composed of acicular α' martensite. Figure 7a,b shows such a microstructure as was also described in other studies [14][15][16][17]20]. The α' martensitic microstructure produced after LMD manufacturing of Ti-6AL-4V is located inside the elongated prior β grains.…”
Section: Laser Metal Deposition (Lmd)supporting
confidence: 77%
“…With a further decrease in temperature, the α phase grows into the β grains, either in a platelet form or along the β grain boundaries, depending on the cooling rate. The cooling rates also affect the size and distribution of α laths inside the prior β grains [15][16][17]. The thickness of α laths decreases if the cooling rates are increased.…”
Section: Parameters Affecting Am Materials Propertiesmentioning
confidence: 99%
“…There are several instances from the literature, which record varying trends of tensile behavior and ductility for the same material printed by DED. For instance, in one study, the tensile strength of DED fabricated Ti-6Al-4V was found to be similar to wrought manufactured Ti-6Al-4V, but with reduced ductility [93]. Another study showed that DED processed Ti-6Al-4V has a higher tensile strength due to a finer microstructure as compared with wrought alloy, but still exhibits lower ductility, due to a combination of the fine microstructure and the presence of internal defects [94].…”
Section: Tensile Strengthmentioning
confidence: 99%
“…To this end, Figure 6 presents the da/dN versus ∆K curves associated with the growth of small cracks given in [40] for post-heat-treated LENS Ti-6Al-4V where the surfaces were not machined. For comparison, Figure 6 also presents:…”
Section: Small Crack Growth In Lens Ti-6al-4vmentioning
confidence: 99%